Assessing Reasonable Accommodation for Persons with Disabilities in Indonesian Prisons: A Constitutional Empirical Study - Sobirin Malian; Heryansyah, Despan; Heronimus Heron (Universitas Islam Negeri Raden Intan Lampung, 2026)
After the promulgation of Law Number 8 of 2016 concerning Persons with Disabilities, law enforcement agencies are obliged to provide reasonable accommodation, including in Correctional Institutions. Reasonable accommodation is the concept of ensuring the rights of persons with disabilities, as introduced by the CRPD and adopted in the Law on Persons with Disabilities. These three obligations are establishing internal regulations for inclusive services, providing accessible facilities and infrastructure, and providing inclusive services. Therefore, this study builds on the IWAS case in Class IIA Correctional Institutions in West Lombok. This study uses a non-doctrinal research method and primary data from direct interviews with persons with disabilities and correctional officers. The results of this research are as follows: the Correctional Unit has issued a set of rules to serve inmates with disabilities in prisons, including in the Class IIA Prison in West Lombok, by creating a Disability Service Unit (ULD) in 2024. Second, in general, the West Lombok Prison provides facilities and infrastructure for inmates with disabilities. However, there are still small areas for improvement; for example, the guiding block has begun to deteriorate, and the toilets are narrow. Third, West Lombok Prison officers still lack the knowledge and skills to handle inmates with disabilities, because the training has been carried out online. Whereas, constitutionally based on Article 28H paragraph (2) of the 1945 Constitution of the Republic of Indonesia, the fulfillment of the rights of every citizen, especially people with disabilities, is a state obligation that must be fulfilled and protected